Pengendalian Alih Fungsi Lahan Pertanian Menjadi Lahan Non Pertanian Berdasarkan Undang-Undang Nomor 41 Tahun 2009 - Rahmanto, Lucius Andik; Muharman, Dedy; Sicillia Anggraini, Novellita (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The purpose of this study is to analyze and analyze the implementation of the conversion of agricultural land to non-agricultural land, and to reconstruct the implementation of the conversion of land to non-agricultural land, based on the value of justice. The research method used is sociological juridical using primary data and secondary data. Based on the results of the study it was found that the implementation of controlling the conversion of agricultural land to non-agricultural land by the government through statutory regulations, especially Law Number 41 of 2009 concerning Protection of Agricultural Sustainable Food Land, has not been commensurate with justice because there is still inequality of position and equal treatment in the law and also the neglect of the rights of farmers as landowners are not considered. Reconstruction of the control value over the conversion of agricultural land to non-agricultural land based on the value of justice is to realize the availability of agricultural land for food self-sufficiency and the availability of agricultural land that is converted into non-agricultural land for the benefit of building public facilities that are evenly distributed, while the legal reconstruction is in Article 44 of Law No. 41 of 2009 concerning Protection of Sustainable Food Agriculture.